2009
DOI: 10.1007/s00244-009-9302-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Environmental Quality of French Continental Mediterranean Lagoons with Oyster Embryo Bioassay

Abstract: Abstract:In order to better understand environmental disturbances in the French coastal Mediterranean lagoons, we used an ecotoxicological approach based on the measurement of the toxicity of the sediments using oyster embryo bioassay that provides a basis for assessing the effects on the fauna of contaminants adsorbed on the sedimentary particles. The study covers all of the main lagoons of the French Mediterranean coasts of Languedoc Roussillon, Camargue, and Provence (Berre and Bolmon lagoons), where 188 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Other in vitro models from marine invertebrates have also been used in marine ecotoxicological studies: oyster embryos (Galgani et al 2009;Mamindy-Pajany et al 2011), sponge primmorphs (Châtel et al 2011) and isolated invertebrate haemocytes (Anderson et al 1997;Cima et al 2004Cima et al , 2008Gopalakrishnan et al 2011;Greco et al 2011). In haemocytes, the study of pollutant effects demonstrated an alteration of parameters such as cell viability, phagocytotic activity, esterase activity or production of reactive oxygen species (Cima et al 2004;Gagnaire et al 2006;Gopalakrishnan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro models from marine invertebrates have also been used in marine ecotoxicological studies: oyster embryos (Galgani et al 2009;Mamindy-Pajany et al 2011), sponge primmorphs (Châtel et al 2011) and isolated invertebrate haemocytes (Anderson et al 1997;Cima et al 2004Cima et al , 2008Gopalakrishnan et al 2011;Greco et al 2011). In haemocytes, the study of pollutant effects demonstrated an alteration of parameters such as cell viability, phagocytotic activity, esterase activity or production of reactive oxygen species (Cima et al 2004;Gagnaire et al 2006;Gopalakrishnan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity includes both free-metals and inorganic complexes as labile fractions (Galgani et al, 2009;Fig. 5.…”
Section: Metal Accumulation Avs and Sediment Toxicitymentioning
confidence: 99%
“…The biotest analysis procedure was performed as described in His et al (1999) which has been shown (Galgani et al, 2009) to be sensitive and suitable for understanding environmental disturbances affecting lagoon biota. Experiments using biotest analysis were carried out under nitrogen flux (using Glove Bag) to prevent any AVS oxidation when samples were submitted to elutriate preparation.…”
Section: Biotestmentioning
confidence: 99%
See 2 more Smart Citations